GOING BEYOND GEO-CULTURAL PROXIMITIES: DISCOVERY OF CULTURE PATTERNS AND MALAYSIAN BTS FANDOM - Mat Yassin, Yuslinda; Mohamed Thaheer, Baby Anusha Nur; Azizam , Abdul Aziz; Mahpuz, Melina (WILAYAH: The International Journal of East Asian Studies, 2024)
The recent global success of K-pop can be attributed to innovative communication strategies, characterized as fan-based, new media- driven, transnational flow approaches reaching out to fans. This study analyzes textual communication and interactions within the online communication of BTS’ fans through Malaysia’s ARMY official Twitter account @BTSMY_ARMY. It also aims to discover fandom activities emerging from this online communication. Through virtual ethnography and quantitative content analysis of 401 tweets, this research identified five distinct cultural patterns that unite Malaysian BTS fans: 1) Fan Account and Fandom Culture, 2) Streaming Parties and Charting Activities, 3) Creation of Fanart and Graphic Edits, 4) Bilingual Communication and 5) Fan Projects and Supportive Initiatives. It can be concluded that these culture patterns are used as a basis for online interaction, engagement, and knowledge sharing among Malaysian BTS fandom, despite linguistic and cultural differences, transcending geographical divides and going beyond geo-cultural proximities.